3(4x+5)+3x-2=-62

Simple and best practice solution for 3(4x+5)+3x-2=-62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+5)+3x-2=-62 equation:


Simplifying
3(4x + 5) + 3x + -2 = -62

Reorder the terms:
3(5 + 4x) + 3x + -2 = -62
(5 * 3 + 4x * 3) + 3x + -2 = -62
(15 + 12x) + 3x + -2 = -62

Reorder the terms:
15 + -2 + 12x + 3x = -62

Combine like terms: 15 + -2 = 13
13 + 12x + 3x = -62

Combine like terms: 12x + 3x = 15x
13 + 15x = -62

Solving
13 + 15x = -62

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 15x = -62 + -13

Combine like terms: 13 + -13 = 0
0 + 15x = -62 + -13
15x = -62 + -13

Combine like terms: -62 + -13 = -75
15x = -75

Divide each side by '15'.
x = -5

Simplifying
x = -5

See similar equations:

| (8.92x/133.8)=(7.17/35.85) | | 5+11x=12x-2 | | 16+5(2c-1)= | | 9=R/2-3 | | x-50+x=180 | | 41x+2=42x-1 | | 2(-2x-2)+x-4=22 | | 4(x-1)-4=22-42 | | y=3000+260x+-4x^2 | | 7-6m=3 | | 6+66=24r | | 2x=3+6 | | -12x+13=-8x+45 | | y=(1500-20x)(2.00+0.20x) | | t=3r-6 | | -6x+6=-12x+24 | | 8x+181=4x+149 | | 1.57/1000 | | -69(x-63)=x+30 | | 55-4x=3 | | 6-2x=3x+51 | | -6x-3=-12x+33 | | 6-2x=6x+51 | | (8x^2+17x)+6x^2=31x^5 | | (8x^2+17x)+6x^2=31x^2 | | -4x+4=x+54 | | 22x+7=15x+42 | | H=-16t^2+80t+4 | | 6x+12=14x-52 | | 9X+Y=9FORY | | (3n+2)(2n+1)=0 | | 6q+4=2q+28 |

Equations solver categories